META-ANALYSIS STUDY: THEORY OF PLANNED BEHAVIOR IN FRAUD BEHAVIOR - Handayani, Putri Fajar; Sartika, Dina (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
As the world agenda in sustainable development, the Sustainable Development Goals (SDGs) have 17 programs that must be achieved by 2030. To achieve these goals, the four pillars of SDGs development the social, economic, environmental, legal, and governance pillars must be integrated. However, the phenomenon of fraud is a serious threat to the posts of law and governance that has the potential to hinder the achievement of goals. The previous research focused to develop the internal control system to reduce fraud, even though individual tendencies to commit fraud have an important role. Therefore, this study is intended to examine individual factors that influence fraud using the theory of planned behavior. Ten of the 53 selected studies were tested through meta-analysis according to the feasibility criteria, the results were attitude toward behavior, and perceived behavioral control had a significant effect on fraud behavior. The highest correlation is in the subjective norm variable, then the attitude toward behavior variable, and the lowest is the perceived behavioral control variable.